Evidence for subduction at 3.8 Ga: Geochemistry of arc-like metabasalts from the southern edge of the Isua Supracrustal Belt - Jenner, Frances; Bennett, Victoria; Nutman, Allen; Friend, Clark; Norman, Marc; Yaxley, Gregory (Chemical Geology)
We present new major and trace element data for rare examples of preserved pillow basalts from a locality of little studied > 3800 Ma rocks at the southwestern edge of the Isua Supracrustal Belt (ISB), West Greenland. The 20 samples have 47.3-59.0 wt.%